ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN PEMBERIAN ASI EKSKLUSIF PADA BAYI - Warsini, Warsini; Pratiwi, Pegita Dwi (Jurnal Kesehatan Holistic, 2017)
The government set minimum service standards for exclusive breastfeeding 80%. Coverage range of exclusive breastfeeding in infants 0-6 months of Central Java in 2015 amounted to 56.1%.. The research objective was to determine the relationship between role of family and mothers motivation for exclusive breastfeeding success. The study was observational analytic with cross sectional design. Large samples of 33 were taken using saturation sampling technique. Showed no statistical relationship between the role of the family and the success of exclusive breastfeeding (OR = 0123; 95% CI 0.014 to 1.046; p = 0.055), and there is a negative relationship and statistically significant between maternal motivation and success of exclusive breastfeeding. The presence of low maternal motivation likely to succeed in exclusive breastfeeding 0.056 times thus lower than the high maternal motivation (OR = 0.056, 95% CI 0.005 to 0.663; p = 0.022). The conclusion of the research there is a significant association between maternal motivation and success of exclusive breastfeeding but there is no relationship between the role of the family and the success of exclusive breastfeeding